(untitled) (Annals of African Medical Research, 2020)
Persistence of symptoms of low back pains and pelvic girdle pains are frequent complaints after pregnancy. Knowledge of back pain prevention and back education is essential for prevention and relief of persistence pains after delivery. The aim is to determine the factors that are associated with persistence of low back/girdle pains after pregnancy, the severity of the pains and measures undertaken by the patients for alleviation of this chronic condition. The study was a cross sectional survey. Ethics approval was obtained from Aminu Kano Teaching Hospital Ethics Committee. Information such as socio demographic characteristics of the clients, persistence and severity of low back pains/pelvic girdle pains after pregnancy and associated risk factors, was asked and documented on a questionnaire. Consecutive, consenting clients were recruited for the survey. Data collected were analyzed using SPSS Version 19. Qualitative data were summarized using frequencies and percentages. χ2 and Fishers’ Exact tests were used, where appropriate, for categorical data. A P value of ≤0.05 was considered significant. During the period, 51 patients with chronic back/pelvic girdle pains or both were recruited. Their mean age (±SD) was 30.9±5.62 years. Bed rest was the most means of relief of low back/pelvic girdle pains. Variables such as advancing age, ethnic group, high parity, educational status and obesity were found to be present and high among patients with persistence of low back/pelvic girdle pains. However, only their employment status was found to be associated with the severity of their pains (χ2 =11.443, P=0.001). The survey showed only employment status was statistically associated with severity of the low back/pelvic girdle pains (χ2 =11.443, P=0.001). Other variables were not associated. There was low knowledge of back pain prevention and back education among the study group.